The properties of gases and liquids - Reid, Robert C. (McGraw-Hill, 1987)
The estimation of physical properties; Pure component constants; Pressure-Volume-Temperature relations of pure gases and liquids; Volumetric properties of mixtures; Thermodynamic properties; Thermodynamic properties of ideal gases; Vapor pressures and enthalpies of vaporization of pure fluids; Fluid phase equilibria in multicomponent systems; Viscosity; Thermal conductivity; Diffusion coefficients; Surface tension.